2019
DOI: 10.1002/cmdc.201900341
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecule Activators of Glucose‐6‐phosphate Dehydrogenase (G6PD) Bridging the Dimer Interface

Abstract: We recently identified AG1, as mall-molecule activatort hat functions by promoting oligomerization of glucose-6-phosphate dehydrogenase (G6PD) to the catalytically competent forms. Biochemical experiments indicatet hat the activation of G6PD by the original hit molecule (AG1) is noncovalent and that one C 2 -symmetric region of the G6PD homodimer is important for ligand function. Consequently,t he disulfide in AG1 is not required for activationo fG 6PD, and an umber of analogues were prepared without this reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Furthermore, AG1 decreases chloroquine or diamide-induced oxidative stress in human erythrocytes. Raub et al [7] studies reported small-molecule activators of G6PD bridging the dimer interface at the structural nicotinamide adenine dinucleotide phosphate (NADP + ) binding sites of two interacting G6PD monomers. Genetic mutation causes reduced efficiency of the dimerization of G6PD monomers affecting its biological activity; in many cases, the pathological effects of G6PD deficiency were not associated with the reduced expression, but reduced binding energy affecting formation of G6PD homodimers (active form), such as class I G6PD variants, associated with chronic nonspherocytic hemolytic anemia (CNSHA), the most severe phenotypic expression of G6PD deficiency [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, AG1 decreases chloroquine or diamide-induced oxidative stress in human erythrocytes. Raub et al [7] studies reported small-molecule activators of G6PD bridging the dimer interface at the structural nicotinamide adenine dinucleotide phosphate (NADP + ) binding sites of two interacting G6PD monomers. Genetic mutation causes reduced efficiency of the dimerization of G6PD monomers affecting its biological activity; in many cases, the pathological effects of G6PD deficiency were not associated with the reduced expression, but reduced binding energy affecting formation of G6PD homodimers (active form), such as class I G6PD variants, associated with chronic nonspherocytic hemolytic anemia (CNSHA), the most severe phenotypic expression of G6PD deficiency [25].…”
Section: Discussionmentioning
confidence: 99%
“…The two domains are linked by an α helix, containing the totally conserved eight-residue peptide that acts as the substrate-binding site (amino acids 198-206) [6]. G6PD is the only enzyme known to have evolved a second NADP+ binding site, close to the dimer interface; this second structural site is essential for maintaining the activity, stability, and oligomeric state of the enzyme [7].…”
Section: Introductionmentioning
confidence: 99%
“…A group of researchers, in 2019, looked at devising therapeutic measures for G6PD deficiency. 44 They postulate that the use of small molecule activators of the enzyme can promote the activity of the enzyme in deficient patients. The primary principle behind this is protein-protein interactions (PPIs).…”
Section: Small Molecule Activatorsmentioning
confidence: 99%
“…Apart from signalling events, the interactome comprises of interactions between the quaternary structure of proteins to modulate enzyme stability, activity and function. 44 Hence the use of small molecules that target this aspect of the interactome is essential in enhancing enzymatic activity of G6PD.…”
Section: Small Molecule Activatorsmentioning
confidence: 99%
See 1 more Smart Citation